Fed Fund Rate: A Dominant Factor of Fortfolio Flows in Southeast Asia - Marino, Wilman San; Badriatin, Tine; Bintang F.D.S., Ignatia (Almana : Jurnal Manajemen dan Bisnis, 2024)
The impact of globalization on cross-country portfolio investment is the high flow of stocks and bonds with the primary goal of taking high yields from rising prices without aiming to own a company. Emerging markets have generally been net recipients of foreign capital in recent decades, including the countries in Southeast Asia consisting of Indonesia, the Philippines, Malaysia, Singapore, and Thailand. The Fed Fund Rate is believed to be the most influential factor in portfolio flows to various emerging market countries. This study will model portfolio equity flows to Southeast Asia over the last 20 years. Model testing uses the moderation analysis process model 4 by Andrew F. Hayes. The findings of this study indicate that the Fed Funds Rate has a greater effect on Southeast Asia's Equity Flows Portfolio than Internal Gross Domestic Product, which indicates the economic strength of a country in Southeast Asia.